The hybrid and multimodal training of graduate students in education - Terçariol, Adriana Aparecida de Lima; Afecto, Romeu; Evaristo, Ingrid Santella; Rosa, Thaís de Almeida; Teixeira, Lucimara de Sousa; da Costa, Carla Xavier; de Andrade, Osmir Pontes; Yara, Renata Cristina Revuelta (Seven Editora, 2024)
This study is an excerpt from the research project entitled "STEAM Education: A Collaborative Construction with Sustainable Educational Robotics", under development with the support of CNPq and presents the experience of offering a discipline, developed, in a hybrid and multimodal way, with a STEAM approach and with a focus on Project-Based Learning. It was offered in the second semester of 2023 to master’s and doctoral students in the Graduate Programs in Education linked to a private university in São Paulo. In this perspective, synchronous meetings were used, via Google Meet, asynchronous activities via Moodle/WhatsApp and face-to-face meetings. DOI:https://doi.org/10.56238/sevened2024.015-019